COMPREHENSIVE ANALYSIS OF NATIONAL DISTRIBUTION IN THE DIGITAL ERA - Surya, Ruswiati; Irianto, Bambang Sugeng (SYNTIFIC, 2025)
Background. The rise of digital technology has significantly transformed the global economy, particularly influencing the distribution systems for goods and services. In Indonesia, national distribution is vital for ensuring price stability and accessible goods across various regions. The digital era presents new possibilities through e-commerce, smart logistics, and data integration, which enhance speed, transparency, and efficiency in distribution. This study aimed to investigate a comprehensive analysis of national distribution in the digital area. Research method. This research utilizes a descriptive-analytical literature review to examine the national distribution system in the digital era, covering logistics, e-commerce, digital technology, public policy, and distribution infrastructure. It analyzes secondary data from credible sources through a systematic search for articles published in the last 5-10 years, in Indonesian and English. The analysis used five stages. Findings. National distribution is reshaped by digital advancements in e-commerce and logistics, enhancing efficiency and market access while meeting consumer demand for speed. In Indonesia, digital distribution improves economic competitiveness and public welfare, supported by government infrastructure and regulations for consumer protection. The private sector fosters innovation, aiding MSMEs in accessing broader markets. However, sustainability challenges, such as carbon emissions, require eco-friendly practices. Future efforts aim for efficient, monitored systems through digital platforms, promoting economic resilience and stability while addressing ethical consumer protection issues for inclusive growth. Conclusion. Success in national distribution depends on collaboration among the government, the private sector, and the community, alongside adaptive policies and sustainable practices for an effective and equitable system.